Early child development in England: Cross-sectional analysis of ASQ®-3 records from the 2-2½-year universal health visiting review using national administrative data (Community Service Dataset, CSDS) - Jung, Jayu; Cattan, Sarah; Powell, Claire; Barlow, Jane; Liu, Mengyun; Clery, Amanda; Mc Grath-Lone, Louise; Bunting, Catherine; Woodman, Jenny (International Journal of Population Data Science, 2025)
Introduction The Ages & Stages Questionnaire 3rd Edition (ASQ®-3) is a tool to measure developmental delay for children aged between 1 - 66 months originally developed in the United States. This measure has been collected in England since 2015 as a part of mandated 2-2½-year health visiting reviews and collated nationally in the Community Services Dataset (CSDS). CSDS is known to be incomplete and to-date there have not been any published analyses of ASQ®-3 held within CSDS. Objectives This study aimed to a) identify a subset of complete child development data for children aged two in England using ASQ®-3 data in CSDS between 2018/19-2020/21; b) use this subset of data to analyse child development age 2-2½-years in England. Methods This study compared counts of ASQ®-3 records in CSDS by local authority and financial quarter against national, publicly available Health Visitor Service Delivery Metrics (HVSDM) to identify local authorities with complete ASQ®-3 records in CSDS. This study described child development in this subset of the data using both a binary cut-off of whether a child reached expected level of development and the continuous ASQ®-3 score. Results Among the 226,505 children from 64 local authorities in the sample with complete ASQ®-3 data, 86.2% met expected level of development. Children from the most deprived neighbourhoods (82.6%), children recorded as Black (78.9%), and boys (81.7%) were less likely to meet expected level of development. Conclusions To fully understand early child development across England, the completeness of ASQ®-3 data in the CSDS requires improvement. Second, in order to interpret the national CSDS data on child development, ASQ®-3 should be standardised and validated in an English context with attention paid to implementation and subsequent referral and support pathways. Our study provides a minimum estimate of children needing developmental support (13.8%), with many more children likely to be experiencing moderate or mild delay but not identified by the ASQ®-3 cut-offs for expected development.